Daily Captured Pattern of Rice Field Rat Using Trap Barrier System Application in Fallow Land - Saputra, Bubun Afif Hidayat Aziz; Sartiami, Dewi; Wiyono, Suryo; Nurmansyah, Ali; Priyambodo, Swastiko (Jurnal Perlindungan Tanaman Indonesia, 2023)
Rice (Oryza sativa) is an important staple crop for more than half of the world's population to fulfill required nutrients. The most important pest in rice crops is the field rat (Rattus argentiventer), which causes damage and significant yield losses during almost every growing season. One method of rat control is the Trap Barrier System (TBS) which consists of fences, mass/multiple live traps, and trap crops and was able to continuously catch rats during the growing season. The objectives of this study were to count rat captured in TBS during one planting season in fallow lands, identify attack source, and calculate rat damage intensity. The study was conducted on one hectare of rice field and number of rat caught were observed daily. Results showed that 4,580 rats were caught, consisting of 57% males and 43% females, with 94% adults and 6% juveniles. Average rat damage intensity was 15% and the highest number of rats caught were in trap 8, 9, and 10 which were located on the north side and had many suitable shelters for rats.